STRATEGI DERADIKALISASI AKUN DAKWAH ISLAM PADA MEDIA INSTAGRAM DI INDONESIA - Armanda Prastiyan Pratama (Jurnal Penelitian Ilmiah INTAJ, 2020)
Nowadays, internet makes the dakwa (teaching others about the beliefs and practices in Islamic faith) more effective and simpler rather than conventional way. Dakwa using internet becomes timeless and less boundary. This research sets aim to understand ideological framework used by those dakwa accounts in media social Indonesia. By using qualitative research methods, this research attempts to observe the text within the media social (especially in Instagram). The data is collected based on research participant.